The antiosteoporosis effect of icariin in ovariectomized rats: a systematic review and meta-analysis - Liu, Yu; Zuo, Haojiang; Liu, Xuewei; Xiong, Jingyuan; Pei, Xiaofang (Cellular and Molecular Biology, 2017)
Herba Epimedii (Yinyanghuo or Horny Goat Weed) is a traditional Chinese medicine widely used in treating osteoporosis. As the major active component, icariin is intensively investigated in the prevention and treatment of osteoporosis in ovariectomized rats. However, misleading conclusions can be generated in animal studies with various experimental designs. Therefore, a systematic review and meta-analysis was performed to evaluate the efficacy of icariin against osteoporosis in ovariectomized rats. PubMed, EMBASE and Chinese National Knowledge Infrastructure databases were searched to identify studies of icariin in ovariectomized rats. Two independent authors selected and reviewed the publications. Data were pooled using a DerSimonian and Laird random-effects model. The results demonstrated that ovariectomized rats treated with icariin had significantly higher bone mineral density (femur and lumbar spine) and lower bone turnover markers (serum alkaline phosphatase and osteocalcin) compared with the ovariectomized control group. For bone histomorphometric parameters, the percentages of trabecular area and trabecular thickness were significantly higher while the trabecular separation was significantly lower in the ovariectomized rats treated with icariin. Based on these results, the presnet study suggested that icariin might possess substantial antiosteoporosis effect in ovariectomized rats. Safety studies and large randomized clinical trials are needed to further support possible clinical applications of icariin in postmenopausal women with osteoporosis.